Nanoformulated essential oils against fungal and mycotoxin contamination of post-harvest commodities: A sustainable and consumer-friendly approach for food safety (Indian Journal of Natural Products and Resources (IJNPR) [Formerly Natural Product Radiance (NPR)], 2025)
Fungal and mycotoxin contaminations are one of the major threats to food security. Looking into the harmful effects of synthetic preservatives, consumers currently prefer to use safer alternatives for food preservation in order to enhance the shelf life of food commodities such as green preservatives. In this context, plant essential oils (EOs) and their bioactive components are gaining prime attention in food preservation to be used as green preservatives due to their broad bioactivity as well as biodegradable nature, favourable safety profile, diverse mode of action and recognition under Generally Recognized As Safe (GRAS) Category. The nanoencapsulation technique would effectively boost the large-scale application of essential oils as food preservatives through the controlled release of bioactive components. The present review presents the recommendations for essential oils and their nanoformulations as sustainable and consumer-friendly approach to ensuring food safety by reducing mould and mycotoxin contamination.